Performance evaluation of the base isolation technique on the blast mitigation of spatial structures - Gowda Kiran, Kuppalli Krishne; Naroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Unpredictable threat and danger may occur in a structural system due to blast loading. Long-span spatial structures are very practical and common in airport terminals, exhibition centers, stadiums, and other public buildings. For high-rise and multi-story structures, horizontal pressure plays a major role in the level of damage to a structure, whereas long-span structures may be influenced by both horizontal and vertical pressure.
Keywords: blast mitigation; isolation technique; spatial structures; public buildings; simulation; LRB; łagodzenie skutków wybuchu; technika izolacji; struktury przestrzenne; budynki publiczne; symulacja